2020
DOI: 10.1063/1.5143779
|View full text |Cite
|
Sign up to set email alerts
|

Cell shape, and not 2D migration, predicts extracellular matrix-driven 3D cell invasion in breast cancer

Abstract: Metastasis, the leading cause of death in cancer patients, requires the invasion of tumor cells through the stroma in response to migratory cues, in part provided by the extracellular matrix (ECM). Recent advances in proteomics have led to the identification of hundreds of ECM proteins, which are more abundant in tumors relative to healthy tissue. Our goal was to develop a pipeline to easily predict which ECM proteins are more likely to have an effect on cancer invasion and metastasis. We evaluated the effect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 34 publications
6
46
0
Order By: Relevance
“…The invasion of cancer cells is a complex process. The change of the cell shape (Lyons et al, 2016;Baskaran et al, 2020), the softening the cell body and/or the nucleus (Fischer et al, 2020), the enzymatic-degradation of the matrix (Gialeli et al, 2011;Wolf and Friedl, 2011), the switch between migration modes (Friedl and Wolf, 2010) are some of well-founded methods that cancer cells use to overcome steric barriers and thus efficiently invade confined networks.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion of cancer cells is a complex process. The change of the cell shape (Lyons et al, 2016;Baskaran et al, 2020), the softening the cell body and/or the nucleus (Fischer et al, 2020), the enzymatic-degradation of the matrix (Gialeli et al, 2011;Wolf and Friedl, 2011), the switch between migration modes (Friedl and Wolf, 2010) are some of well-founded methods that cancer cells use to overcome steric barriers and thus efficiently invade confined networks.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-ECM responses are studied in vitro using recombinant proteins, evaluating cell adhesion to, migration on, and invasion in individual ECM proteins. We have recently shown that cell shape when a cell is adhering to ECM protein is more predictive of three-dimensional (3D) invasion in response to that same protein than migration on the same 2D substrate ( 19 ). While these assays are informative and can be used to dissect the signaling pathways involved in ECM-driven responses, they also only evaluate response to a single cue.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these results demonstrate that K + channel-driven RMP hyperpolarization drives significant changes in gene expression, upregulation of pathways involved in cell adhesion. The observed upregulation of genes involved in cell adhesion suggests that overexpression of K + channels may alter the adhesion and morphology of TNBC cells, which our lab and others have demonstrated is highly predictive of 3D invasive behavior driving metastasis 34,35 . We characterized cell area and morphology of MDA-MB-231 K + overexpressing lines cultured on collagen I-coated glass plates.…”
Section: K + Channel-driven Rmp Hyperpolarization Drives Upregulation Of Genes Associated With Cell Adhesion and Mapk Signalingmentioning
confidence: 56%